2019
DOI: 10.33952/2542-0720-2019-3-19-49-56
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Agricultural Practices on the Number of Soil Fauna and Productivity of Agricultural Crops

Abstract: Воронин А. Н., Котяк П. А. ВЛИЯНИЕ РАЗНЫХ АГРОПРИЁМОВ НА ЧИСЛЕННОСТЬ ПОЧВЕННОЙ ФАУНЫ И ПРОДУКТИВНОСТЬ СЕЛЬСКОХОЗЯЙСТВЕННЫХ КУЛЬТУР ФГБОУ ВО «Ярославская государственная сельскохозяйственная академия» Реферат. Почвенная фауна -это информативный и доступный для исследований показатель биологических свойств почв. Животные, обитающие в почве, очень остро реагируют на любые изменения среды своего обитания. Цель исследований -определить влияние разных систем обработки почвы и удобрений на численность почвенной фауны… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, crop residues increased soil microarthropod abundance but had no significant effect on biodiversity in loamy sand 14 ; another study on soil meso- and microarthropods in tidal soil reported that straw returned to wheat–maize fields reduced the number of soil faunal groups 15 . However, in another study, the return of crop residues with synthetic fertilizer, nitrogen, phosphorus and potassium, caused a significant decrease in the number of nematodes and an increase in the number of earthworms and ground beetles in sod-podzolic gley mid-loamy soil 7 . Straw return provided richer living conditions, and the dominant groups, including Oribatida and Actinedida, accounted for 77.1% of the meso- and microfauna population in black soil 16 , while the dominant groups in fluvo-aquic soils were Collembola and Acari, which accounted for nearly 80% 17 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, crop residues increased soil microarthropod abundance but had no significant effect on biodiversity in loamy sand 14 ; another study on soil meso- and microarthropods in tidal soil reported that straw returned to wheat–maize fields reduced the number of soil faunal groups 15 . However, in another study, the return of crop residues with synthetic fertilizer, nitrogen, phosphorus and potassium, caused a significant decrease in the number of nematodes and an increase in the number of earthworms and ground beetles in sod-podzolic gley mid-loamy soil 7 . Straw return provided richer living conditions, and the dominant groups, including Oribatida and Actinedida, accounted for 77.1% of the meso- and microfauna population in black soil 16 , while the dominant groups in fluvo-aquic soils were Collembola and Acari, which accounted for nearly 80% 17 .…”
Section: Introductionmentioning
confidence: 93%
“…Soil fauna are highly diverse, which are generally divided into microfauna, mesofauna, macrofauna and megafauna based on different body widths 6 . They are sensitive to changes in their habitat 7 , such as fertilizer use, tillage, and multiple species, i.e., earthworms and oribatids can be used as biological indicators to indicate changes in soil fertility and quality 8 .…”
Section: Introductionmentioning
confidence: 99%